(untitled) (SALAM Digest: Syariah and Law Undergraduate Symposium, 2024)
This article highlights the challenges faced by the Shariah Courts in Malaysia, which continue to encounter issues in the application of Islamic law. As Muslims, adhering to Islamic law is both a duty and an obligation that cannot be separated from daily life. Islam strictly opposes any form of tyranny and injustice, ensuring that cruelty is never tolerated. This study also aims to counter the negative perception that Shariah Courts are secondary in terms of power and effectiveness compared to other judicial institutions in Malaysia. Using a qualitative approach, this research relies on secondary sources, including statutory provisions, scholarly articles, and online resources. It examines existing legal provisions and suggests improvements in key areas to establish a more systematic approach to alternative sentencing in the Shariah Courts. The findings of this study reinforce the role of Shariah Courts as a primary legal reference for Muslims in matters such as criminal offenses, marriage, and property disputes. Strengthening the Shariah judicial system ensures that justice is properly administered, and that the Shariah Courts are respected institutions, upheld by all communities. Ultimately, as Islamic law is derived from Allah SWT, it remains the most just and perfect legal system for humanity.